The relationship between the accuracy of nurse triage and initial stabilization time in pediatric emergency patients in the emergency department - Yosafat Barus; Dedy Sambahtrah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Pediatric emergency care in the Emergency Department (ER) requires rapid and appropriate treatment because children are highly susceptible to delays in treatment. Accurate nurse triage is a crucial factor in determining treatment priority and the speed of initial patient stabilization. Purpose: To determine the relationship between the accuracy of nurse triage and the initial stabilization time of pediatric emergency patients in the Emergency Room. Method: This study used an observational analytical design with a cross-sectional approach. The study was conducted in the Emergency Room of Bina Kasih Hospital in October–November 2025 with 25 pediatric emergency patients as respondents. The sampling technique used total sampling. Data were collected through observations of nurse triage accuracy and recording of initial stabilization times based on the ABC principle. Data analysis was performed using univariate and bivariate methods with a significance level of p < 0.05. Results: The results showed that most nurses performed triage correctly and that most pediatric emergency patients achieved rapid initial stabilization times. Bivariate analysis revealed a significant association between nurse triage accuracy and initial stabilization times in pediatric emergency patients in the emergency department. Conclusion: There is a significant relationship between nurse triage accuracy and initial stabilization time in pediatric emergency patients. Accurate triage plays a crucial role in accelerating initial treatment and improving the quality of pediatric emergency services.